2012
DOI: 10.1111/j.1471-6712.2012.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Meaning of work and the returning process after breast cancer: a longitudinal study of 56 women

Abstract: The meaning of work varies over time, but first and foremost work was regarded as an important part of the healing process as it restores the disruption of everyday life. Guidelines cannot be reduced to a linear relationship with biomedical variables but the individual context of everyday life must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 30 publications
3
59
0
2
Order By: Relevance
“…This finding supports similar previous research that reported that returning to work was regarded as an important part of the healing process because it restores everyday life (Lilliehorn et al . ). Returning to work can: (1) turn a patient's attention away from her disease; (2) allow patients to keep up with society, provide them with a fuller life, and produce more confidence and psychological strength; and (3) increase household income.…”
Section: Discussionmentioning
confidence: 97%
“…This finding supports similar previous research that reported that returning to work was regarded as an important part of the healing process because it restores everyday life (Lilliehorn et al . ). Returning to work can: (1) turn a patient's attention away from her disease; (2) allow patients to keep up with society, provide them with a fuller life, and produce more confidence and psychological strength; and (3) increase household income.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is also quite evident that there are several barriers and challenges for HNC patients in the process of rehabilitation and resuming everyday life, including feelings of anxiety, potential job loss, pressure to return to work too early, feelings of loneliness, being poorly understood, and feeling abandoned. In order to avoid such experiences, it seems vital that the patients experience health care as a 'secure base' or a 'helping system/helping plan' [4,30], which, in turn, can facilitate the patients' 'biographical repair' [27], including the return to work. Because many HNC patients are affected by both physical and psychological distress, a rehabilitation plan provided by the health care system might be important in preventing job loss and in helping the individual to find strategies to be able to return to work as well as in strengthening the patients' feelings of security.…”
Section: Discussionmentioning
confidence: 99%
“…Returning to work is important for overall psychological and physical well-being in addition to the financial implications of returning to work [2,3]. Work is thus considered an important part of the healing process, but the meaning of work for the patients might vary before diagnosis and during and after sick leave [4]. In addition, not being able to work might interfere with daily life routines and might lead to a lack of confidence and to social isolation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Given the evidence that working contributes to an individual's sense of self and quality of life [22,23], as well as protects against financial distress, it is important that HNC survivors are aware that return to work is possible but may take an extended period of time. Clinicians should be aware that workforce participation should be considered from the time of diagnosis, and may continue to be an issue during and beyond the period of rehabilitation.…”
Section: Workforce Participation Rates Over Timementioning
confidence: 99%
“…Similarly qualitative research has found that workforce participation following cancer is not a linear concept [22,23].…”
Section: Workforce Participation Rates Over Timementioning
confidence: 99%